Heat Transfer Correlations for compressible flow in Micro Heat Exchangers. Issue 3 (September 2016) - Coppola, M. A.; Croce, G.
Abstract: The paper discusses the definition of dimensionless parameters useful to define a local correlation for convective heat transfer in compressible, micro scale gaseous flows. A combination of static and stagnation temperatures is chosen, as it allows to weight the temperature change related to the heat transfer and that induced by conversion of internal energy into kinetic one. The correlation offers a purely convective local Nusselt number, i.e. correlating the heat flow rate with the local flow parameters and wall surface temperature. The correlation is validated through a series of numerical computations in both counter-current and co-current micro heat exchanger configurations. The numerical computations take into account rarefaction and conjugate heat transfer effects.